2016
DOI: 10.1155/2016/4391375
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Natural Nootropics: Recent Molecular Enhancement Influenced by Natural Nootropic

Abstract: Nootropics or smart drugs are well-known compounds or supplements that enhance the cognitive performance. They work by increasing the mental function such as memory, creativity, motivation, and attention. Recent researches were focused on establishing a new potential nootropic derived from synthetic and natural products. The influence of nootropic in the brain has been studied widely. The nootropic affects the brain performances through number of mechanisms or pathways, for example, dopaminergic pathway. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 124 publications
(137 reference statements)
1
48
0
4
Order By: Relevance
“…There are two types of nootropics: synthetic or natural compounds. While both have been widely researched and can effectively increase functions such as memory and attention, natural nootropics are associated with a safer side-effect profile and are even capable of making the brain healthier (see Suliman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of nootropics: synthetic or natural compounds. While both have been widely researched and can effectively increase functions such as memory and attention, natural nootropics are associated with a safer side-effect profile and are even capable of making the brain healthier (see Suliman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Piracetam exerts its action by enhancing cell membrane permeability and increase oxygen consumption by elevating the adenylate kinase activity in brain. 26,27 This drug is mainly used to treat a wide range of neurological abnormalities like seizures, epilepsy, myoclonus, dementia, myoclonus or Alzhemier's disease, multi infarct dementias, senile dementia, alcoholism, Parkinson's diseases etc. It has reported that piracetam produces neuro plasticity and it enhances memory and learning process thereby preventing lesions and ischemic damages.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, pharmacological therapies have long been considered the best therapeutic option available for treating PD as the drug treatment has proved to be the one with the best results. Different herbal products have been evaluated throughout the years, and some have reached outstanding results such as M. pruriens , V. faba , Camelia sinensis , and G. biloba (Tanaka et al , ; Suliman et al , ).…”
Section: Discussionmentioning
confidence: 99%